Phenotypic plasticity of Chinese sprangletop (Leptochloa chinensis) in competition with seeded rice - Chauhan, Bhagirath S.; Johnson, David E. (Cambridge University Press, 2011)
Chinese sprangletop, a C4species, is one of the most important grass weeds of seeded rice in Asia. Chinese sprangletop biology was studied by growing it alone and in competition with 4 and 12 rice plants. Rice competition did not affect the height of Chinese sprangletop, and the weed grew taller than rice, regardless of the competition. Compared with Chinese sprangletop grown alone, competition from rice reduced Chinese sprangletop leaf number, leaf production rate, tiller number, tiller production rate, leaf area, shoot biomass, relative growth rate, and net assimilation rate. Leaf area and shoot biomass of Chinese sprangletop when grown in competition with 12 rice plants was only 16% and 13%, respectively, of the leaf area and biomass of the weed grown alone.